Development of an automated system for making multi-stage management decisions at industrial enterprises - Solodovnik, Ganna; Deynega, Alena (Technology audit and production reserves, 2020)
The object of research is the process of making managerial decisions, which requires an analysis of the sequence of decisions and external factors, in the case when one set of strategies of the subject of control and states of the external environment generates another state of this type. The study is devoted to the issues of automation of management processes of socio-economic systems, namely, the creation of a model and software implementation of the process of making multi-stage decisions at a manufacturing enterprise. The production system is a complex dynamic system, therefore it is characterized by uncertainty in its functioning, as well as a large number of heterogeneous elements and connections, multivariate development. These characteristics of the system, as well as the fundamental uncertainty of external factors of functioning, necessitate the analysis of a large amount of information, which is inherent in uncertainty and incompleteness. Therefore, it is important to create automated management decision-making support systems. The objective of research is to create a rational choice model in a situation where there are two (or more) sequential sets of decisions, and subsequent decisions are based on the results of the previous ones. This situation assumes the presence of two (or more) multiple states of the external environment. That is, a whole chain of decisions appears, arising from each other and corresponding to events that occur with a certain probability. To solve this type of problem, the game-theoretic apparatus of multi-stage games with nature is used. In order to carry out experiments with the model, its software implementation has been developed. The paper reviews the existing analogues, analyzes the input and output data of the model. Within the framework of the object-oriented programming methodology, an activity diagram is built, the functionality of the actors is determined, and a description of the functional model is made. By conducting experiments with the model, it is possible to improve the validity of management decisions. The advantages of the developed automated system in comparison with known analogues: support for multi-stage management decisions, providing opportunities for saving and correcting results.